Developing Islamic Economic and Finance Literacy among Insurance Brokers - Dede Abdul Fatah; Inas Afifah Zahra; Bambang Waluyo; Khalda Abidaturrahman; Wanda Mutia; Arka Balacosa Argyyndra (Jurnal Pengabdian Masyarakat dan Penelitian Thawalib)
Islamic economics and finance are experiencing rapid global growth; however, literacy within Indonesia’s insurance brokerage sector remains low, necessitating empowerment initiatives to enhance understanding and compliance with Sharia principles. This community empowerment initiative aims to improve Islamic economic and financial literacy among insurance brokers by introducing the principles of Sharia contracts and examining the potentials and challenges of the Islamic insurance brokerage industry. The workshop was held on July 4, 2025, at PT. Perisai Bhakti Raharjo involved 29 participants and employed a participatory approach combining interactive lectures, case discussions, and group-based problem-solving sessions. The outcomes significantly improved participants’ understanding of Sharia financial concepts. The majority could differentiate between conventional and Islamic insurance, comprehend the role of Islamic insurance brokers, and recognize the application of Sharia contracts in financial transactions. These findings indicate that community-based, participatory learning effectively enhances Sharia financial literacy and professional competence, particularly in underexplored sectors such as insurance brokerage. This workshop is a practical reference and a replicable model for similar initiatives to increase Sharia compliance awareness within Indonesia’s financial sector. In conclusion, the Islamic Economic and Finance Literacy Workshop for Insurance Brokers improved participants’ understanding of the challenges and opportunities within the Islamic insurance industry, the foundational Islamic legal principles, and the application of Sharia-compliant contractual mechanisms.